OPTIMAL CAPITAL STRUCTURE ANALYSIS FOR PT PERKEBUNAN NUSANTARA VII - , Heru Wijayanto ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The lower cost of capital the higher the firm value. Company should consider the cost of capital in order to develop the optimal capital structure since it can maximize value of the firm. Investing program that involve large number of external financial source make PTPN VII needs to consider whether the capital structure in 2009 was optimal and how much the optimal capital structure. The main purpose of this research is to determine the optimal capital structure of PTPN VII by considering several factors influencing. This research will be conducted based on financial data of PPTN VII in 2009, Business Plan of PTPN VII 20010-2014 and data of economy and plantation industry. Data collection use record analysis which is a form of non behavioral observation. The research use Discounted Cash Flow method of income approach on valuation. In 2009, PTPN VII has debt to equity ratio 127% with cost of capital was 11.70%. The optimal capital structure rest on about 150% debts to equity ratio or when company use 60% of debt and 40% of equity. It means PTPN VII has spear to use more debt for financing the investment program. However average capital structure of plantation industry was about 70% which was much lower than PTPN VII. Currently, management does not heavily concern on optimal level of capital structure since the company needs large number of fund for improving planted area profile and prioritizing the fund availability.